An accurate on-site calibration system for electronic voltage transformers using a standard capacitor. (27th March 2018) - Hu, Chen; Chen, Mian-zhou; Li, Hong-bin; Zhang, Zhu; Jiao, Yang; Shao, Haiming
Abstract: Ordinarily electronic voltage transformers (EVTs) are calibrated off-line and the calibration procedure requires complex switching operations, which will influence the reliability of the power grid and induce large economic losses. To overcome this problem, this paper investigates a 110 kV on-site calibration system for EVTs, including a standard channel, a calibrated channel and a PC equipped with the LabView environment. The standard channel employs a standard capacitor and an analogue integrating circuit to reconstruct the primary voltage signal. Moreover, an adaptive full-phase discrete Fourier transform (DFT) algorithm is proposed to extract electrical parameters. The algorithm involves the process of extracting the frequency of the grid, adjusting the operation points, and calculating the results using DFT. In addition, an insulated automatic lifting device is designed to realize the live connection of the standard capacitor, which is driven by a wireless remote controller. A performance test of the capacitor verifies the accurateness of the standard capacitor. A system calibration test shows that the system ratio error is less than 0.04% and the phase error is below 2′, which meets the requirement of the 0.2 accuracy class. Finally, the developed calibration system was used in a substation, and the field test data validates the availability of the system.